'Go with the flow' for gamification and sustainability marketing. (December 2021) - Whittaker, Lucas; Mulcahy, Rory; Russell-Bennett, Rebekah
Highlights: Flow influences customer engagement and value-in-behavior within gamification. Customer engagement is an antecedent of value creation within gamification.. Customer engagement and value-in-behavior are mediators within gamification. App replay and sustainable behavior intentions are influenced by value-in-behavior. Value can be created beyond gameplay and towards sustainable behavior. Abstract: This paper explores the potential of gamification for sustainability marketing efforts, examining users' experiences with a gamified app designed to encourage the sustainable energy behavior of turning off electricity switches. Using data collected from 387 participants who partook in a week-long field study using a gamified app, we analyze the interrelationships between flow, customer engagement, value-in behavior, and intentions to perform sustainable behavior and continue use of a gamified app. We show how consumers' gameful experiences via flow enhance engagement with a gamified app, and how this results in enhancing the perceptions of value in performing a sustainable energy behavior. Further, we evidence how the value-in-behavior created by a gamified app not only influence behavioral intentions to perform a sustainable energy behavior, but also intentions to continue using the gamified app. These results provide important theoretical and practical insights as to the potential for gamification to be used for sustainability marketing and how gameful experiences (flow and customer engagement) can transfer to positive perceptions of sustainable behavior (value-in-behavior).